All-HKMG-bounded SCR for advanced ESD protection in 14 nm FinFET technology. (1st August 2022) - Du, Feibo; Xie, Tiantian; Wang, Jun; Chang, Kuan-Chang; Lin, Xinnan; Hou, Fei; Chen, Ruibo; Han, Aoran; Liu, Zhiwei
Abstract: In this paper, a novel all-high- K metal gate (HKMG)-bounded silicon-controlled rectifier (AHBSCR) is proposed for advanced electrostatic discharge (ESD) protection in FinFET processes. Depart from its prior arts, in AHBSCR, both the main SCR path and the triggering diode path are placed along the Fin direction, and all active areas are bounded by HKMG, thus expressing superior conduction capability under various ESD stresses and a more compact silicon footprint. Experimental results show that the proposed AHBSCR owns a suitable snapback window of 1.1 V–1.6 V, a fast turn-on speed of only 400 ps, an extreme low leakage current of less than 100 pA@-1 V as well as a figure of merit of 24.3 mA fF −1, indicating it is competent to replace the conventional FinFET diodes in rail-based ESD network to further improve the efficiency of ESD protection.